2022
DOI: 10.1002/adfm.202110393
|View full text |Cite
|
Sign up to set email alerts
|

Yellow‐Emissive Carbon Dots with High Solid‐State Photoluminescence

Abstract: Carbon dots (CDs) present an enticing prospect for a variety of optical applications relying on their high photoluminescence (PL) quantum yield (QY). Herein, the synthesis, optical properties, structural characterizations, density‐functional theory (DFT) calculations, and potential applications of yellow‐emissive CDs (Y‐CDs) with ultra‐high PL QY are reported. Solvothermal treatment of citric acid and urea in toluene, followed by column chromatography, produces Y‐CDs exhibiting excitation‐independent PL emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 71 publications
(133 reference statements)
1
67
0
Order By: Relevance
“…As reported so far, all CA/U-CDs obtained by pyrolysis, microwave irradiation, or hydrothermal treatment display blue or green fluorescent emission, which originates from individual molecular fluorophores as well as from their self-assembly into H-bonded or covalently linked aggregates. Interestingly, CA/U-CDs with emission at longer wavelengths have also been achieved by replacing water with DMF , ,, or toluene . In the work of Hu et al, it is shown that the autoclave thermal treatment of 1.0 g of citric acid and 2.0 g of urea in 10 mL of DMF can produce CA/U-CDs with tunable emission, from blue to red, by increasing the reaction temperature .…”
Section: Ca-cd Classessupporting
confidence: 56%
See 1 more Smart Citation
“…As reported so far, all CA/U-CDs obtained by pyrolysis, microwave irradiation, or hydrothermal treatment display blue or green fluorescent emission, which originates from individual molecular fluorophores as well as from their self-assembly into H-bonded or covalently linked aggregates. Interestingly, CA/U-CDs with emission at longer wavelengths have also been achieved by replacing water with DMF , ,, or toluene . In the work of Hu et al, it is shown that the autoclave thermal treatment of 1.0 g of citric acid and 2.0 g of urea in 10 mL of DMF can produce CA/U-CDs with tunable emission, from blue to red, by increasing the reaction temperature .…”
Section: Ca-cd Classessupporting
confidence: 56%
“…Interestingly, CA/ U-CDs with emission at longer wavelengths have also been achieved by replacing water with DMF 18,78−80,89,90 or toluene. 91 In the work of Hu et al, it is shown that the autoclave thermal treatment of 1.0 g of citric acid and 2.0 g of urea in 10 mL of DMF can produce CA/U-CDs with tunable emission, from blue to red, by increasing the reaction temperature. 80 Similar observations are present in the work of Miao et al, who also reported that higher citric acid/urea ratios can red-shift the final CA/U-CD emission.…”
Section: Ca-cd Classesmentioning
confidence: 99%
“…The N 1s spectra (Figure d) present three peaks located at 397.7, 398.6, and 399.6 eV, corresponding to the Ti–N bond, pyridinic N and pyrrolic N, further confirming the successful doping of nitrogen. The Ti 2p spectrum of N-MQDs/CdS exist five peaks, which belong to Ti–N bond (456.4 eV), Ti-Cbond (461.3, 455.4 eV) and Ti–O bond (464.4, 458.5 eV). , Apparently, the formation of Ti–N confirms the successful N doping in Ti 3 C 2 MXene quantum dots (Figure e). The C 1s spectra of pure CdS (Figure S9) show peaks at 284.7, 286.2, and 288.8 eV attributed to C–C/CC, C–O, and CO bonds, respectively . Compared with pure CdS, the extra peak in N-MQDs/CdS at 283.8 eV attributed to C–Ti bond (Figure f), which further evidence the successful compounding of N-MQDs and CdS.…”
Section: Resultsmentioning
confidence: 86%
“…[ 6 ] To date, various CDs have been developed and efficient blue, green, and red emissions have been achieved in several CDs systems. [ 7 ] However, efficient NIR‐emissive CDs have rarely been reported. [ 8 ] The initial attempt was to synthesize NIR‐emissive CDs from high price NIR‐emissive organic dyes.…”
Section: Introductionmentioning
confidence: 99%